PELATIHAN PEMANFAATAN LIMBAH DURI BANDENG SEBAGAI BAHAN PEMBUATAN KRUPUK STIK DI KELURAHAN GUNUNG ANYAR TAMBAK KECAMATAN RUNGKUT SURABAYA - Kustini, Kustini; Yuniningsih, Yuniningsih; Winarti, Sri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
Micro Small Enterprises (MSEs) act as a strategic force and have an important position, both in employment, community welfare, adhesiveness and stabilizing the problem of social inequality. The results of the preliminary field survey, showed that in Gunung Anyar Urban Village, Surabaya ponds, they have a pond cultivation business, especially milkfish cultivation and other fish. Fish farming results in addition to being sold in the form of raw fish are also processed in various kinds of processed fish, for example fish crackers, fish thorns, bandeng gapit and shredded fish. Various businesses, especially the business of removing thorns, cause problems, namely the increasing waste of milkfish thorns, especially from milkfish as well as thorns. Based on these problems, this paper aims to utilize the milk thorn waste into economic value so that it can increase people's income. The method used is the classical method and community development or community development in the Gunung Anyar Tambak village, Surabaya. Results of the East Java Thematic Community Service Program